1984
DOI: 10.1111/j.1399-0004.1984.tb02016.x
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial deletion of band q12 of chromosome 5

Abstract: A six‐months‐old girl is presented with psychomotor retardation and multiple congenital malformations. The karyotype done on peripheral blood lymphocytes and skin fibroblasts was found to be 46,XX del(5)(411q13). The parents are consanguineous. Their karyotypes were normal. The genes for Arylsulphatase B and Hexosaminidase B are not located in band 5q12.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
2

Year Published

1991
1991
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
2
2
Order By: Relevance
“…Ocular findings were reported in a 5q11q13 deletion and included ptosis, epicanthus, astigmatism, convergent strabismus, and nystagmus (Adduction Fixation Preference) [Mansour et al, 1984]. Overall, the reported cases of 5q deletions were not associated with a recognizable phenotype [Silengo et al, 1981; Dudin et al, 1984] but in contrast to our study, ocular features were not reported as a major characteristic. It should be noted, for further genotype–phenotype correlations, that these 5q deletions were estimated only by banding techniques and, therefore, not precisely mapped.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Ocular findings were reported in a 5q11q13 deletion and included ptosis, epicanthus, astigmatism, convergent strabismus, and nystagmus (Adduction Fixation Preference) [Mansour et al, 1984]. Overall, the reported cases of 5q deletions were not associated with a recognizable phenotype [Silengo et al, 1981; Dudin et al, 1984] but in contrast to our study, ocular features were not reported as a major characteristic. It should be noted, for further genotype–phenotype correlations, that these 5q deletions were estimated only by banding techniques and, therefore, not precisely mapped.…”
Section: Discussioncontrasting
confidence: 87%
“…Proximal 5q cytogenetically visible deletions including 5q12 have been reported in only few patients. Dudin et al [1984] described a case with psychomotor retardation and dysmorphic features. Ocular findings were reported in a 5q11q13 deletion and included ptosis, epicanthus, astigmatism, convergent strabismus, and nystagmus (Adduction Fixation Preference) [Mansour et al, 1984].…”
Section: Discussionmentioning
confidence: 99%
“…There are also case reports of deletions of chromosome 5q13 (Dudin et al 1984, Herrera et al 1986, Stoll et al 1980) and chromosome 21q22 (Modi & Buckton 1982), lacking any similarity to our patient more specific than those common in most cases of chromosomal aberration.…”
Section: De Iiovo 5;21 Translocation and Congenital Malformationscontrasting
confidence: 67%
“…accepted for publication 4 June 1997 A limited number of (interstitial) deletions on the long arm of chromosome 5 have been described (Schinzel 1994). The most proximal breakpoint in these deletions is at 5qll (Dudin et al 1984), and the most distal at 5q35.3 (Stratton et al 1994). The number of identical or similar deletions is too small to allow description of a recognisable syndrome stemming from a 5q-deletion.…”
mentioning
confidence: 98%